Failed state discourse under international law: the place, attributes and implications - Dube, Brian; Manatsa, Proceed (2016)
This paper laments the failure by international instruments including the Geneva Conventions to define a failed State. It thus seeks to provide a comprehensive definition of what constitutes a failed State under International law. In so doing, the article brings to light the attributes and features of a failed State from different dimensions, ranging from political, historical, and developmental to sociological perspectives. Intrinsically, the paper is an endeavor to answer the following questions; what is a failed State and who decides that a State has failed? What are the effects of the failed State discourse on international law? What is the place or legal status of a failed State on the international plane? The article also seeks to demonstrate how the very existence of a failed State discourse can affect state representation in international organizations, diplomatic law, judicial competence, treaty-making powers, international security, compliance with international obligations and issues of state responsibility in the promotion of human security under international law. As a final point, the paper will furnish the international community with a solid analytical base from which to generate high-quality response strategies to foster international peace, security and development. The understanding of a failed State discourse and efforts for preventing states from failing, and resuscitating those that have failed all strategic and moral imperatives for fostering global peace and development on earth.